Putra Learning Hub: a one-stop centre for flexible and open education (FLEX-ED) - Ismail, Alyani; Ma'rof, Aini Marina; Saad, Wan Zuhainis; Abdul Rashid, Mohd Idham; Zamzuri, Mohd Zainal; Shukri, Radhiah; Zulkafli, Arina Zafirah; Konting, Mohd Majid (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Putra Learning Hub is a one-stop portal being developed as the hub of e-Learning at Universiti Putra Malaysia (UPM) and has been officially launched in April 2016. This flexible learning hub is a platform for academic staffs and students to acquire the latest developments of Digital Education at the university to support 21st Century Teaching and Learning.